Rationale for the Use of Cord Blood in Hypoxic-Ischaemic Encephalopathy - Izabela Zdolińska-Malinowska; Dariusz Boruczkowski; Dominika Hołowaty; Paweł Krajewski; Emilian Snarski (Stem Cells International)
Hypoxic-ischaemic encephalopathy (HIE) is a severe complication of asphyxia at birth. Therapeutic hypothermia, the standard method for HIE prevention, is effective in only 50% of the cases. As the understanding of the immunological basis of these changes increases, experiments have begun with the use of cord blood (CB) because of its neuroprotective properties. Mechanisms for the neuroprotective effects of CB stem cells include antiapoptotic and anti-inflammatory actions, stimulation of angiogenesis, production of trophic factors, and mitochondrial donation. In several animal models of HIE, CB decreased oxidative stress, cell death markers, CD4+ T cell infiltration, and microglial activation; restored normal brain metabolic activity; promoted neurogenesis; improved myelination; and increased the proportion of mature oligodendrocytes, neuron numbers in the motor cortex and somatosensory cortex, and brain weight. These observations translate into motor strength, limb function, gait, and cognitive function and behaviour. In humans, the efficacy and safety of CB administration were reported in a few early clinical studies which confirmed the feasibility and safety of this intervention for up to 10 years. The results of these studies showed an improvement in the developmental outcomes over hypothermia. Two phase-2 clinical studies are ongoing under the United States regulations, namely one controlled study and one blinded study.